Zinc Oxide as an Active Ingredient in Sensitive Skin Deodorant - Roslan, Fatin Khadijah; Taib, Clijster; Azhar, Alif Aiman; Ab Razak, Siti Noraiza (Multidisciplinary Applied Research and Innovation, 2025)
This study investigates the benefits of Zinc Oxide (ZnO) as an active ingredient in deodorant, replacing aluminium (Al) compounds that usually present in conventional deodorant that caused harmful effects to human skin. The goals of this study are to produce a sensitive skin friendly-deodorant using ZnO powder as the main ingredient. Besides, sweet almond oil (SAO), tea tree oil (TTO) and essential oil (EO) were added as an alternative ingredients to help in neutralize body odour and absorbance of sweat. The deodorant was made using heating process and was analysed qualitative and quantitatively. The chemical properties were analysed via Fourier-transform infrared spectroscopy (FTIR) and pH meter. In addition, yellow stain testing was also performed to analyse the quality of the deodorant. At the end of this project, a survey was conducted among Tun Hussein Onn University of Malaysia (UTHM) students to collect their opinion on the deodorant. From the analysis, it is found that the ether compounds are the main compound lies within 3020 cm-1 to 2870 cm-1 wavelengths based on FTIR analysis. The pH value of ZnO deodorant was measured at pH 7; make it safe to be used on direct skin without any skin irritation. ZnO deodorant was also tested on white cloth within 7 days observation and leaved partially visible white stain on the cloth that is easily removed using cold water. This study concluded that ZnO is a beneficial alternative in deodorant and consumer’s feedback shows a positive reception to the new formulation of the deodorant.